Adverse events among high-risk participants in a home-based walking study: a descriptive study - Holleman Robert G; Lowery Julie C; Larkin Angela R; Goodrich David E; Richardson Caroline R (BMC, 2007)
Abstract Background For high-risk individuals and their healthcare providers, finding the right balance between promoting physical activity and minimizing the risk of adverse events can be difficult. More information on the prevalence and influence of adverse events is needed to improve providers' ability to prescribe effective and safe exercise programs for their patients. Methods This study describes the type and severity of adverse events reported by participants with cardiovascular disease or at-risk for cardiovascular disease that occurred during an unsupervised, home-based walking study. This multi-site, randomized controlled trial tested the feasibility of a diet and lifestyle activity intervention over 1.5 years. At month 13, 274 eligible participants (male veterans) were recruited who were ambulatory, BMI > 28, and reporting one or more cardiovascular disease risk factors. All participants attended five, face-to-face dietitian-delivered counseling sessions during the six-month intervention. Participants were randomized to three study arms: 1) time-based walking goals, 2) simple pedometer-based walking goals, and 3) enhanced pedometer-based walking goals with Internet-mediated feedback. Two physicians verified adverse event symptom coding. Results Enrolled participants had an average of five medical comorbidities. During 1110 person months of observation, 87 of 274 participants reported 121 adverse events. One serious study-related adverse event (atrial fibrillation) was reported; the individual resumed study participation within three days. Non-serious, study related adverse events made up 12% of all symptoms - predominantly minor musculoskeletal events. Serious, non-study related adverse events represented 32% of all symptoms while non-serious, non-study related adverse events made up 56% of symptoms. Cardiovascular disease events represented over half of the non-study related adverse event symptoms followed by musculoskeletal complaints. Adverse events caused 50 temporary suspensions averaging 26 days in duration before physician medical clearance was obtained to resume walking. Conclusion Men at high risk for adverse cardiovascular events can safely be advised to start a progressive walking program. Results suggest that minor to serious medical problems unrelated to exercise are a major barrier to walking adherence. Helping individuals with chronic illness return to physical activity quickly but safely after an adverse event is an important component of any physical activity intervention targeting this population.